Factors Affecting Student Stress Levels after a Year of the Covid-19 Pandemic - Risda Rizkillah; Rika Rahmawati (Psympathic : Jurnal Ilmiah Psikologi, 2022)
The period of Covid-19 pandemic brought about numerous life-altering events for students. Therefore, this research aims to analyze the effect of student characteristics, problems, social support, and coping strategies on stress levels after one year of the pandemic. Quantitative method was used with a cross-sectional design to obtain 879 Indonesian students through a voluntary sampling technique. The results showed that there was a significant positive effect of student characteristics and problems on stress levels. Furthermore, there is a significant negative effect of social support and coping strategies on student stress levels.